Role of Metal Contacts on Halide Perovskite Memristors - Pérez Martínez, José Carlos (2023)
Halide perovskites are promising candidates for resistive memories (memristors) due to their mixed electronic/ionic conductivity and the real activation mechanism is currently under debate. In order to unveil the role of the metal contact and its connection with the activation process, four model systems are screened on halide perovskite memristors: Nearly inert metals (Au and Pt), low reactivity contacts (Cu), highly reactive contact (Ag and Al), and pre-oxidized metal in the form of AgI. It is revealed that the threshold voltage for activation of the memory effect is highly connected with the electrochemical activity of the metals. Redox/capacitive peaks are observed for reactive metals at positive potentials and charged ions are formed that can follow the electrical field. Activation proceeds by formation of conductive filaments, either by the direct migration of the charged metals or by an increase in the concentration of halide vacancies generated by this electrochemical reaction. Importantly, the use of pre-oxidized Ag+ ions leads to very low threshold voltages of ≈0.2 V indicating that an additional electrochemical reaction is not needed in this system to activate the memristor. Overall, the effect of the metal contact is clarified, and it is revealed that AgI is a very promising interfacial layer for low-energy applications.